Northern Nigeria: Sheep and goat production in the traditional Fulani agropastoral sector - Otchere, E.O.; Ahmed, H.U.; Adenowo, T.K.; Kallah, M.S.; Bawa, E.L.K.; Olorunju, S.A.S.; Voh, A.A. (1987)
Data are presented on the performance of Yankasa sheep and Red Sokoto goats kept by Fulani pastoralistst in a traditional agropastoral system in north Nigeria. Some comparisons are made with data from other studies in Nigeria and various West African countries. It is evident that small ruminant, especially goats, are important in providing ready cash for small household requirements. Management, nutrition and pre-weaning mortality are the main constraints to increased productivity, and efforts should be made to develop low-cost, low technology assistance in these areas.